2023
DOI: 10.1002/ohn.336
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Year Outcomes After Pediatric In‐Office Tympanostomy Using Lidocaine/Epinephrine Iontophoresis and an Automated Tube Delivery System

Abstract: ObjectiveEvaluate 2‐year outcomes after lidocaine/epinephrine iontophoresis and tympanostomy using an automated tube delivery system for pediatric tube placement in‐office.Study DesignProspective, single‐arm.SettingEighteen otolaryngology practices.MethodsChildren age 6 months to 12 years indicated for tympanostomy were enrolled between October 2017 and February 2019. Local anesthesia of the tympanic membrane was achieved via lidocaine/epinephrine iontophoresis and tympanostomy was completed using an automated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…One study have showed that there was no difference between tube extrusion, tympanic membrane perforation, and tube occlusion under GA or LA. 35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study have showed that there was no difference between tube extrusion, tympanic membrane perforation, and tube occlusion under GA or LA. 35…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term follow‐up regarding children's fear of doctors and/or medical staff will also be evaluated. One study have showed that there was no difference between tube extrusion, tympanic membrane perforation, and tube occlusion under GA or LA 35 …”
Section: Discussionmentioning
confidence: 99%